Seasonality of above-ground net primary productivity along an Andean altitudinal transect in Peru. (November 2014) - Girardin, C. A. J.; Malhi, Y.; Feeley, K. J.; Rapp, J. M.; Silman, M. R.; Meir, P.; Huaraca Huasco, W.; Salinas, N.; Mamani, M.; Silva-Espejo, J. E.; García Cabrera, K.; Farfan Rios, W.; et al.
Abstract: Solar irradiance and precipitation are the most likely drivers of the seasonal variation of net primary productivity (NPP) in tropical forests. Since their roles remain poorly understood, we use litter traps, dendrometer bands and census data collected from one hectare permanent plots to quantify the seasonality of above-ground NPP components and weather parameters in 13 sites distributed along a 2800-m altitudinal gradient ranging from lowland Amazonia to the high Andes. We combine canopy leaf area index and litterfall data to describe the seasonality of canopy production. We hypothesize that solar irradiance is the primary driver of canopy phenology in wetter sites, whereas precipitation drives phenology in drier systems. The seasonal rhythm of canopy NPP components is in synchrony with solar irradiance at all altitudes. Leaf litterfall peaks in the late dry season, both in lowland (averaging 0.54 ± 0.08 Mg C ha y−1, n = 5) and montane forests (averaging 0.29 ± 0.04 Mg C ha y−1, n = 8). Peaks in above-ground coarse woody NPP appears to be triggered by the onset of rainfall in seasonal lowland rain forests (averaging 0.26 ± 0.04 Mg C ha y−1, n = 5, in November), but not in montane cloud forests.